Bidang Hukum dalam Sistem Pembiayaan Modal Ventura - Indrajaya Indrajaya (Wajah Hukum, 2020)
In reality, the main obstacle for small business actors is related to the problem of providing capital. To overcome this, the Government issued policies in the economic field, one of which was the government policy regarding the establishment of funding institutions as stipulated in the Presidential Regulation. One form of financial institution in question is Venture capital which is regulated in the Minister of finance regulation. As one of the companies engaged in the field of financing services, the approach is not only limited to the economy, but is also needed in the form of law. so that it can be recognized in the business world. Although the agreement is considered as the main legal source of venture capital in civil law, nevertheless, given its role in the field of financing services that many involve the public interest, its existence is also inseparable from the regulation of public law. This study aims to analyze whatever legal fields are involved in the Venture Capital financing system. While the problem in this research is what legal fields apply in the Venture Capital financing system. This research is a normative legal research, using primary legal materials, secondary legal materials and tertiary legal materials. The approach taken is by statute approach and conceptual approach. From the results of the study it can be concluded that the applicable law in the Venture Capital financing system is the field of civil law, specifically regarding the principle of freedom of contract and the provisions of the Civil Code and the field of public law.